Impact of Enhanced Detection on the Increase in Thyroid Cancer Incidence in the United States: Review of Incidence Trends by Socioeconomic Status Within the Surveillance, Epidemiology, and End Results Registry, 1980–2008 - Li, Nan (Mary Ann Liebert, Inc., 2013)
BACKGROUND: In the past 3 decades, the incidence of thyroid cancer in the United States has been increasing. There has been debate on whether the increase is real or an artifact of improved diagnostic scrutiny. Our hypothesis is that both improved detection and a real increase have contributed to the increase. METHODS: Because socioeconomic status (SES) may be a surrogate for access to diagnostic technology, we compared thyroid cancer incidence trends between high- and low-SES counties within the Surveillance, Epidemiology, and End Results 9 (SEER 9) registries. The incidence trends were assessed using joinpoint regression analysis. RESULTS: In high-SES counties, thyroid cancer incidence increased moderately (annual percentage change 1 [APC1]=2.5, p<0.05) before the late 1990s and more pronounced (APC2=6.3, p<0.05) after the late 1990s. In low-SES counties, incidence increased steadily with an APC of 3.5 (p<0.05) during the entire study period (1980–2008). For tumors ≤4.0 cm, incidence was higher in high-SES counties, and APC was higher for high- than low-SES counties after the late 1990s. For tumors >4.0 cm, high- and low-SES counties had similar increasing incidence trends. Similarly, for tumors ≤2.0 cm, the incidence trends differed between counties that are in or adjacent to metropolitan areas and counties that are in rural areas, whereas for tumors >2.0 cm, all counties regardless of area of residence had similar increasing trends. CONCLUSIONS: Enhanced detection likely contributed to the increased thyroid cancer incidence in the past decades, but cannot fully explain the increase, suggesting that a true increase exists. Efforts should be made to identify the cause of this true increase.